Latin American Week in London. - ICA (Institute of Contemporary Arts), London (Buenos Aires : CAYC - Centro de Arte Y Comunicacion, 1974)
Puppo, Hector ; Dujovny, Gregorio ; Porter, Liliana ; etc.
Latin American Week in London, ICA (Institute of Contemporary Arts), London, November 28th - December 6th, 1974
boek
Keywords: Latijns Amerika